Ocular Manifestations, Visual Field Pattern, and Visual Field Test Performance in Traumatic Brain Injury and Stroke - Yun Jeong Lee; Seung Chan Lee; Seo Young Wy; Hoo Young Lee; Hyang Lim Lee; Woo Hyung Lee; Byung-Mo Oh; Jin Wook Jeoung (Journal of Ophthalmology)
Purpose. To analyze ocular manifestations, visual field (VF) pattern, and VF test performance in traumatic brain injury (TBI) and stroke patients. Methods. This retrospective, cross-sectional study included 118 patients (236 eyes) with TBI and stroke who had undergone VF testing by standard automated perimetry with the central 24-2 threshold test. Clinical features including best-corrected visual acuity (BCVA), intraocular pressure (IOP), ocular manifestations, and VF test results including VF defect pattern, reliability, and global indices were analyzed and compared between the TBI and stroke patients. Results. In TBI patients, ocular manifestations included strabismus (11.1%), cataract (4.2%), and glaucoma suspect (2.8%), whereas in stroke patients, cataract (15.2%), strabismus (8.5%), diabetic retinopathy (4.9%), extraocular movement (EOM) limitation (3.0%), glaucoma suspect (3.0%), nystagmus (2.4%), drusen (1.2%), and vitreous hemorrhage (1.2%) were found. The VF test results showed that 47 eyes (85.5%) in TBI and 86 (65.2%) in stroke had VF defect; in TBI, the scattered pattern was the most common (56.4%), followed by homonymous hemianopsia (14.5%), homonymous quadrantanopia (10.9%), and total defect (3.6%), whereas in stroke, homonymous hemianopsia was the most common (31.8%), followed by scattered pattern (16.7%), homonymous quadrantanopia (12.1%), and total defect (4.5%). Only 15 eyes (27.3%) in TBI and 32 (24.2%) in stroke showed reliable VF indices. The mean deviation (MD) was −10.5 ± 7.1 dB in TBI and −9.5 ± 6.8 dB in stroke, and the pattern standard deviation (PSD) was 4.9 ± 3.3 dB in TBI and 6.1 ± 3.9 dB in stroke, without statistically significant differences between the two groups. Conclusion. Various ocular manifestations were found, and a considerable proportion of patients were experiencing VF defects and showed unreliable VF test performance. Our findings suggest that accurate evaluation and rehabilitation of visual function should be a matter of greater concern and emphasis in the management of TBI and stroke patients, besides systemic diseases.